CNVs de novo no cromossomo x da prole em resposta a exposição parental a baixas doses de radiação ionizante - Rodrigue, Lucas Henrique Nascimento Silva (2019)
A radiological accident occurred in Goiânia-GO in 1987, exposed hundreds of people at high and low doses of ionizing radiation. When there is this type of exposure, the cells can undergo chemical, physical and biological damage, also causing genomic damage ranging from nucleotide exchange to double-strand breaks. In order to repair such DNA damage, repair processes are activated by recombining the genome and can bring about several genomic changes, such as variations in the number of copies, which arise from mutational events and are mostly normal or disease-causing variations. to some factor (again) or inherited. This study analyzed CNVs again on the X chromosome of individuals whose one of their parents had accidental exposure to low dose 137Cs (≤ 0.2Gy). The group consisted of 8 families with at least one parent exposed, resulting in a total of 12 children born after exposure to low dose ionizing radiation and 10 families with no history of radiation exposure to make up the control group. After blood collection, chromosome analysis was performed on microarray (CMA) using GeneChip® CytoScanHDTM (Affymetrix, USA) and soon after the X chromome analysis was performed using ChAS® software followed by statistical analysis. In the exposed group, 251 CNVs were found again on the X chromosome, an increase of about 2.5x compared to the control group and CNVs gain was 4.3x higher in the exposed group (p = 0.003). When the parental origins were observed, 50% of new and validated CNVs are of maternal origin and in most families the mother was accidentally exposed to IR. However, this study allowed to observe a higher rate of genomic gains in relation to X chromosome losses in the offspring of individuals exposed to low doses of ionizing radiation. Maternal age was shown to be related to the CNV rate of loss in the offspring. However, the increase in CNVs again may be indicative that the radiation has increased the rate of DNA damage after parental exposure. In the literature there is no information on CNVs on the X chromosome of individuals exposed to radiation, making this work unprecedented.